2014
DOI: 10.1016/j.intell.2013.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Quality of institutions: Does intelligence matter?

Abstract: We analyze the eect of the average level of intelligence on dierent measures of the quality of institutions, using a 2006 cross-sectional sample of 113 countries. The results show that average IQ positively aects all the measures of institutional quality considered in our study, namely government eciency, regulatory quality, rule of law, political stability and voice and accountability. The positive eect of intelligence is robust to controlling for other determinants of institutional quality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
15

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(37 citation statements)
references
References 24 publications
1
21
0
15
Order By: Relevance
“…From a macroeconomic perspective, it may be feasible to increase the quality of political institutions through investing in cognitive skills and education. Indeed, recent publications claim that nations with higher IQ have better rule of law (Kanyama, 2014) and lower corruption (Potrafke, 2012). From a political viewpoint the results of this study may be elucidated in line with Glaeser et al (2007) who show that human capital increases the benefits of civic participation.…”
Section: Indirect Relationship Of Intelligencesupporting
confidence: 66%
See 1 more Smart Citation
“…From a macroeconomic perspective, it may be feasible to increase the quality of political institutions through investing in cognitive skills and education. Indeed, recent publications claim that nations with higher IQ have better rule of law (Kanyama, 2014) and lower corruption (Potrafke, 2012). From a political viewpoint the results of this study may be elucidated in line with Glaeser et al (2007) who show that human capital increases the benefits of civic participation.…”
Section: Indirect Relationship Of Intelligencesupporting
confidence: 66%
“…In this study we hypothesize that the benefit of intelligence builds up either through the quality of institutions, or through civic participation among citizens. Indeed, related literature demonstrates that intelligence is an important determinant of institutional arrangements (Kanyama, 2014;Salahodjaev, 2015a). For example, in early empirical articles intelligence, measured by the Army General Classification Test, is positively linked with the rule of law at the US state level (Davenport & Remmers, 1950).…”
Section: Introductionmentioning
confidence: 99%
“…In a similar vein, Nikolaev and Salahodjaev (2016), using data from 81 countries and 50 US states, showed that intelligence leads to a more equal distribution of wellbeing within society. Moreover, at the macro-social level intelligence contributes to economic growth (Ram, 2007), quality of government institutions (Kanyama, 2014), good governance, environmental protection (Obydenkova, Nazarov & Salahodjaev, 2016) and the wealth of nations (Rindermann, Kodila-Tedika and Christainsen, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a number of follow up papers find that cognitive abilities are instrumental to antecedents of economic growth such as institutions (Kanyama, 2014) and credit sector size (Kodila-Tedika & Asongu, 2015) and corruption (Potrafke, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In a follow up study, Salahodjaev (2015c) analyzing data from more than 150 nations finds that cognitive skills have a negative effect on the size of the informal sector relative to GDP. Furthermore, studies find a positive correlations between intelligence and governance indicators (Kanyama, 2014) and freedom (Meisenberg, 2012;Meisenberg, 2014).…”
Section: Introductionmentioning
confidence: 99%